P(A U B) = ?

Asked by  | 16th Jun, 2008, 02:01: PM

Expert Answer:

P(A U B) = P(A) + P(B) - P(A ∩ B)

P(A) = Probabiltiy that number greater than 3 (4, 5, 6) is obtained = 3/6

P(B) = Probability that number less than 5 (1,2,3,4) is obtained = 4/6

P(A ∩ B) = Probability that number greater than 3 and less than 5 (4) is obtained  = 1/6

Thus P(A U B) = 3/6 + 4/6 - 1/6 = 1

Answered by  | 18th Jun, 2008, 10:33: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.